Statelessness: the absence of nationality and the construction of a Brazilian policy of hospitality - Assunção, Thiago (2018)
Statelessness, or lack of nationality, affects more than 10 million people in the world today. The main objective of this thesis is to shed light on the phenomenon of statelessness, departing from the study of the role of nationality, and its relationship with the exercise of citizenship. Initially, it is contextualized historically the emergence of the nation-state, as well as the principle of nationality, connected to state sovereignty. Subsequently, it is studied the criteria used for the attribution of nationality by the states, as well as the progressive limits to their discretion in this area. The phenomenon of statelessness is then explored, starting from its history, concept, causes and consequences. It is elucidated the answers built in international law for its reduction and protection of stateless persons. Finally, the challenges for eradicating statelessness in the world are studied. In a second moment, the thesis problematizes the very notions of nationality and citizenship, to analyze how the transformations in progress in the international scenario have affected these institutes. Based on the study of globalization, regional integration, transnationality of non-state actors, the emergence of human rights and the rise of the individual as subject of international law, as well as the intensification of international human mobility, the work seeks to analyze the impact of these factors on nationality and the exercise of citizenship. In particular, it is revealed the emergence of new forms of belonging and association of the individuals, related to the pluralism that characterizes the identities in contemporaneity. This trend points to an internationalization of citizenship, especially considering the growing affirmation of the human rights of non-citizens. In addition, naturalization and multiple nationality are increasingly regulated by international law, in the light of the principle of non-discrimination and individual autonomy. The study seeks to understand the existence of a communitarian citizenship in Europe, from the supranationality of the European Union, as well as the emergence of what the doctrine calls global, transnational or post-national citizenship, from the detachment of the nationality from the citizenship. Finally, the work points to the construction of a (human) right to citizenship. In the last chapter, the thesis presents Brazil as a case study, based on the category of hospitality in relation to the Other. The recent initiatives of reception of migrants and refugees in the country are analyzed, in the search to build a migration and asylum policy compatible with the international commitments assumed, as well as with the Brazilian tradition of country of migrations. Finally, the legal framework of statelessness in Brazil is presented, with a brief analysis of the new migratory law, especially in regard to the unprecedented regulation of statelessness in the country, which, it is concluded, matches with the construction of a Brazilian policy of hospitality.